Personality Traits and Voluntary Leaving Organization in Selected Government Establishments in Akwa Ibom State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study was designed to examine the relationship between personality traits and voluntary leaving organization in selected government establishments in Akwa Ibom State.  To achieve the study objective, a survey research design was used. The population of the study consisted 90 senior staff in personnel Department from the Ministries of Agriculture, Finance and Information in Akwa Ibom State. A total sample size of 60 respondents were selected using stratified random sampling technique. Data were collected through questionnaire titled “Personality Traits and Voluntary Leaving Organization Questionnaire (PTVLOQ)” carefully designed and administered to the respondents. A total of 60 copies of questionnaire were distributed to respondents, out of which 58 copies were returned and found to be correctly filled. Data collected were analyzed using tables, simple percentage and Regression.  The result of the study showed a positive significant relationship between personality traits and voluntary leaving organization in selected government establishments in ty.ectiveness in organization'toor management of personnel.ibilities , assignment of the right jobs to wrong and unq Akwa Ibom State. The findings also revealed that employees who scored high in openness to experience as well as neuroticism are bound to make a voluntary decision to leave their organizations. It was recommended from the study that, government establishments in Akwa Ibom State should introduce and maintain a fair and effective reward system for outstanding performances so as to motivate employees to always put in their best and remain in their organizations.